Efektifi tas Ekstrak Kulit Manggis (Garcinia Mangostana) terhadap Jumlah Sel NK dan Kadar Ifn-γ pada Penderita HIV di RSUD Cirebon - MARIA DYAH KURNIASARI; EDI DHARMANA; MUHAMAD HUSEIN GASSEM (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
Mangosteen peel contains xanthone as antioxidant, useful as prooxidant balancer. The activity of xathone can be found from the number of NK cells that will increase the production of IFN-γ cytokine. The human experimental research has been done by Randomized Control Group Pretest-Post Test Design, 20 patients sample for each group. Mann Whitney test was used to determine the diff erences between the group 1 & group 2. The Spearman’s Rho Test was used to determine the correlation between the NK cells number and IFN-γ level. There are no signifi cant diff erences between NK cell number (p:0.911) and IFN-γ level (p:0.588) in the pre and post test examination after have been given mangosteen peel extract. There are no signifi cant correlations between NK cell number and IFN-γ level in each group (p: 0.074). There are no eff ects of giving mangosteen peel extract on the number of NK cell and IFN-γ level to HIV patients.